2019
DOI: 10.1111/dom.13937
|View full text |Cite
|
Sign up to set email alerts
|

Differences between patients with type 1 diabetes with optimal and suboptimal glycaemic control: A real‐world study of more than 30 000 patients in a US electronic health record database

Abstract: Aims To use electronic health record data from real‐world clinical practice to assess demographics, clinical characteristics and disease burden of adults with type 1 diabetes (T1D) in the United States. Materials and methods Retrospective observational study of adults with T1D for ≥24 months at their first visit with a T1D diagnosis code (“index date”) between July 2014 and June 2016 in the Optum Humedica database. Demographic characteristics, acute complications (severe hypoglycaemia [SH], diabetic ketoacidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
(50 reference statements)
0
13
2
Order By: Relevance
“…This finding is of concern, and more emphasis on smoking cessation and prevention programs may be warranted in the management of these patients. Of note, while our population compares poorly with some [ 23 , 34 ], some cohorts in other countries have also shown a similar or higher prevalence of smoking [ 14 , 17 ], suggesting the importance of smoking interventions elsewhere and in general. Finally, the prevalence of overweight and obesity was higher than previously reported [ 35 ], mirroring the increased prevalence of this emerging risk factor in the background population.…”
Section: Discussioncontrasting
confidence: 59%
“…This finding is of concern, and more emphasis on smoking cessation and prevention programs may be warranted in the management of these patients. Of note, while our population compares poorly with some [ 23 , 34 ], some cohorts in other countries have also shown a similar or higher prevalence of smoking [ 14 , 17 ], suggesting the importance of smoking interventions elsewhere and in general. Finally, the prevalence of overweight and obesity was higher than previously reported [ 35 ], mirroring the increased prevalence of this emerging risk factor in the background population.…”
Section: Discussioncontrasting
confidence: 59%
“…hypertension, dyslipidemia), the CACTI study identified obesity as a risk factor for both the presence and progression of coronary artery calcifications independent of pre-existing metabolic abnormalities ( 106 ). How this translates to long-term cardiovascular morbidity and mortality is less clear ( 107 ). The Pittsburgh EDC study demonstrated that waist circumference, a surrogate of visceral adiposity, increases the risk for long-term mortality in type 1 diabetes ( 108 ).…”
Section: Added Risk For Micro- and Macrovascular Complicationsmentioning
confidence: 99%
“…In type 1 diabetes (T1D), several large-scale population registries have emerged, including the Swedish National Diabetes Register (NDR), 1 the Diabetes-Patienen-Verlaufsdokumentation databases (DPV), 2 the German Diabetes Versorgungs-Evaluation (DIVE), 3 and others. 4,5 In the past decade, the Type 1 Diabetes Exchange Clinic Registry (T1DX), 6 an invited clinic-based cooperative, and the Optum Humedica database 7 have provided similar reports in the United States. In Canada, the Canadian Study of Longevity in T1D has particularly studied adults with T1D >50 years.…”
Section: Introductionmentioning
confidence: 99%
“…6,[10][11][12][13] For example, several registries have recently updated their reports to again confirm that even with recent advances in therapies and technologies, only a minority actually achieves recommended targets. 7,10,11 An accurate and constant awareness of the clinical status of people with T1D is necessary to inform the feasibility of current guidelines and the need for future strategy redevelopment. The Canadian LMC Diabetes Registry comprises the health records of one of the largest endocrine practice groups globally, with >50 endocrinologists across three Canadian provinces.…”
Section: Introductionmentioning
confidence: 99%